The Effects Of A Vocal Music Metacognition E-Learning (Vm-Mel) Module On Music Metacognitive Awareness, Self-Directed Learning And Singing Performance Achievement Of Preschool Education College Students In China - Li, Wen (2025)
In recent years, e-learning has increasingly been adopted as a learning mode in vocal music education. However, the transition from traditional face-to-face teaching to online environments presents multiple challenges. Teachers often struggle to adapt to new instructional methods, and students frequently lack effective self-directed learning (sdl) strategies. Research highlights metacognition as a crucial method for enhancing sdl and academic performance in e-learning settings. Accordingly, this study developed the vocal music metacognition e-learning (vm-mel) module, which combines metacognitive and sdl strategies to enhance learners' metacognitive awareness, sdl capabilities, and singing performance. Using a quasi-experimental design, this research compared the performance of an experimental group (38 participants) with a control group (42 participants) before and after an eight-week training programme, supplemented by interviews with participants to evaluate the instructional effectiveness of the vm-mel module. The results revealed that vm-mel significantly improved students' metacognitive awareness, sdl, and singing performance. The vm-mel module, offers practical teaching and sdl strategies for music educators and students. The widespread adoption of this module will ensure equitable learning opportunities for learners, enabling them to study independently at any time and place.